Understanding the large heterogeneity in hospital readmissions and mortality for acute myocardial infarction. Issue 7 (July 2020) - Lobo, Mariana F; Azzone, Vanessa; Lopes, Fernando; Freitas, Alberto; Costa-Pereira, Altamiro; Normand, Sharon-Lise; Teixeira-Pinto, Armando
Highlights: After adjusting for patient risk factors, mortality and readmission probabilities differ substantially across hospitals. High mortality hospitals encompass a 91% increased death risk compared to low mortality hospitals. High readmitting hospitals encompass a 46% increased risk of readmission compared to low readmitting hospitals. Hospital location, caseload, and size are associated with disparities in AMI health outcomes. Abstract: This study aims to investigate the variation in two acute myocardial infarction (AMI) outcomes across public hospitals in Portugal. In-hospital mortality and 30-day unplanned readmissions were studied using two distinct AMI cohorts of adults discharged from all acute care public hospital centers in Portugal from 2012−2015. Hierarchical generalized linear models were used to assess the association between patient and hospital characteristics and hospital variability in the two outcomes. Our findings indicate that hospitals are not performing homogeneously—the risk of adverse events tends to be consistently larger in some hospitals and consistently lower in other hospitals. While patient characteristics accounted for a larger share of the explained between-hospital variance, hospital characteristics explain an additional 8% and 10% of hospital heterogeneity in the mortality and the readmission cohorts respectively. Admissions to hospitals with low AMI caseloads or located in Alentejo/Algarve and Lisbon had a higher risk of mortality. Discharges from larger-sized hospitals were associated with increased risk of readmissions. Future health policies should incorporate these findings in order to incentivize more consistent health care outcomes across hospitals. Further investigation addressing geographical disparities, hospital caseload and practices is needed to direct actions of improvement to specific hospitals.